Transition in action: toward a social theory of the governance of transitions - Billi, Marco; Zurbriggen, Cristina; Urquiza, Anahí; Allendes, Angel (Frontiers in Sociology, 2024)
This article explores how a re-interpretation of the socio-technical, socio-ecological and transition design approaches to transition from the point of view of Niklas Luhmann’s general systems theory of society. The need to understand and promote changes that include a technological and ecological dimension has led to different approaches, such as socio-technical or socio-environmental approaches, to incorporate links with society. While these approaches often include sociological insights, they rarely offer a general understanding of how these are embedded into society. We need a new environmental sociology that helps catalyze change processes with a collectively reorganized society, empowering more radically transformative actions to change the current structures and processes that have led us to where we are today. The article offers a cross-sectional look at the socio-ecological and socio-technical systems literature, specifically for what concerns their understanding of the ‘systems’ in transition and how they can be governed, and re-interpret it from the theoretical lens of the deep sociological knowledge, which refers to the profound understanding of social systems and their dynamics, embedded in Luhmann’s theory of social systems. From here, we suggest the second-order coupling for a sociologically grounded understanding of the interactions that comprise socio-ecological and socio-technical systems, heterogeneous and almost self-organizing assemblies of social, technical, and natural elements and processes. At the same time, third-order couplings are analyzed, focused on governance, relationships between operations, and structures mediated by a deliberate attempt to ensure coherence and coordination against the autonomy and heterogeneity of socio-techno-ecological systems. Therefore, this manuscript offers a deeper conceptual and methodological understanding of socio-techno-ecological couplings and systems in the context of sustainability transformation and gives insights into its governance.